PENGELOLAAN FASILITAS OBJEK WISATA PEMANDIAN TIRTA ALAMI KABUPATEN PADANG PARIAMAN - Davinky, Ikrar; Yuliana, Yuliana; Waryono, Waryono (Journal of Home Economics and Tourism, 2016)
This research aimed to describe: (a) planning, (b) organizing, (c) direction and (d) supervision in the tourist bathing Tirta Alami Padang Pariaman district. Describe the aspects of facilities management based attractions such as (a) restaurant facilities, (b) and shopping facilities (c) facilities at tourist sites attractions baths Tirta Alami. This type of research is descriptive qualitative data. Data was collected using observation, interviews, and documentation involving informants inside that one person led part tourist attraction manager baths Tirta Alami, one staff manager attractions baths Tirta Alami, one community manager of the restaurant, and one community manager shopping facilities, a research instrument that determines the research instruments, data reduction, data presentation. Based on the results of the study found several issues related to the management of the facility attractions: 1) Attraction manager and manager of the baths Tirta Alami Attraction restaurants surrounding communities do not have a good plan for the future. 2) Attraction business already has a restaurant employee organization for the field of work each, 3) Managers control of the attraction of the restaurant focused on building control, employee and the restaurant menu. 4) Attraction business tirta baths naturally do briefed on employees and building rehabilitation. The results of the study suggested that leadership part tourism managers Tirta Alami Padang Pariaman district is already planning work for one year, organizing clear for employees attractions baths Tirta Alami, monitoring regularly and strict supervision of employees and provide sanctions for employees break and give rewards for employees who abide by the regulations attractions that management can function properly.Keywords: Management, Facilities, Attractions